Care and consumption. Issue 2 (9th November 2022) - Godin, Laurence
Abstract : In this article, I argue that care is a useful tool to think about consumption as embedded in social relations within and outside the market, and draw the consequences for moving towards sustainable lifestyles. To do so, I engage in a review of the literature that brings together consumption and care in its various forms. I review three main bodies of work: the literature on consumption that links care to consumer behaviour and consumption practices; the work addressing the commodifications of care and how it feeds in the neoliberal organisation of society; and the literature on climate change and the development of sustainable lifestyles. I close with a reflection on some lessons of care for academic researchers studying sustainability, consumption and a transition towards more sustainable and just societies.